مقارنة متعددة الأسس بين الإيزوفلوران والبروبوفول كمساعد في التخدير باستخدام الريميفنتانيل كأساس تخديري. - إبراهيم, رزق الله; إبراهيم, تيسير; خدام, أيهم (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في مشفى الأسد الجامعي في اللاذقية في قسم التخدير و الإنعاش خلال العام 2006-2007 وتضمنت 100 مريضٍ، 50 مريضاً خضع لعملية جراحية كبرى تحت التخدير العام بالإيزوفلوران مضافاً إلى الريميفنتانيل، و50 آخرون باستخدام البربوفول كمساعد في التخدير باستخدام الريميفنتانيل كأساس. و كانت نتائج الدراسة على النحو الآتي: التخدير بالريميفنتانيل مشاركاً مع مخدر طيار أو مخدر وريدي فعال ومتحمَّل بشكل جيد. يعد كل من الإيزوفلوران أو البربوفول مناسباً كمساعد إضافي للريميفنتانيل والجرعات المطبقة متكافئة سريرياً من جهة الصحو و الإفاقة وبناءً عليه أن المشاركتين المذكورتين ملائمتان تماماً على اعتبار أن الصحو السريع من التخدير مفضل ومرغوب به جداً (كالكلام أو الحركة بعد الجراحة ). أزمنة نزع الأنبوب والصحو من التخدير والخروج من غرفة الإنعاش كانت قصيرة الأمد. الصحو بعد إعطاء الريميفنتانيل- ايزوفلوران على الأقل أسرع من الريميفنتانيل - بروبوفول . This study was carried out in the Department of anesthesia and reanimation at ALASSAD University Hospital in Lattakia during 2006-2007, and included (100 ) patients. (50) patients had a large operation done under general anesthesia with Isoflurane in addition to Remifentanil, whereas (50) patients had it with Propofol as adjuncts to Remifentanil-based Anesthesia. The results showed that anesthesia combining remifentanil with volatile hypnotics or total intravenous anesthesia (TIVA) with propofol was effective and well tolerated. Both Isoflurane and Propofol are suitable adjuncts to Remifentanil, and the applied dosages are clinically equivalent with respect to emergence and recovery. Both combinations should be appropriate, particularly in settings in which rapid recovery from anesthesia is desirable, such as fast talking and/or ambulatory surgery. Times of extubation, post anesthesia recovery and recovery room discharge were rapid. Emergence after Remifentanil-based anesthesia with Isoflurane is at least as rapid as with Propofol.